Influence of Dhikr Therapy on Reducing Signs and Symptoms of Halucinations in Hallucination Patients in Regional Psychiatric Hospital Dr. Arif Zainudin Surakarta - Lestari, Miki; Gati, Norman Wijaya; Purnomo, Luluk (Jurnal Kegawatdaruratan Medis Indonesia, 2023)
The increasing prevalence of schizophrenic patients is as much as 7% of the Indonesian population and around 70% of schizophrenic patients experience hallucinations. hallucinations are false perceptions, clients with hallucinations often feel a state that can only be felt by them but cannot be felt by other people. in minimizing the impact caused by hallucinations, proper treatment is needed, one of which is dhikr therapy, where dhikr therapy can relieve anxiety, anxiety and calm the heart. This research aim to dhikr therapy for reducing signs and symptoms in halucinations patient. The research design used in this research is a descriptive research design in the form of a case study by providing AHRS observation sheets. The level of hallucinations before the dhikr therapy was carried out, the patient was in the category of signs and symptoms of severe hallucinations. after dhikr therapy the patient experienced mild hallucinations. there are differences in the development of signs and symptoms of hallucinations before and after the application of dhikr therapy. There is a comparison of development between patients who experience signs and symptoms of hallucinations before and after being given dhikr therapy.